2017
DOI: 10.3989/ajbm.2455
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic relationships within the Maghrebian clade of <em>Festuca</em> subgen. <em>Schedonorus</em> (Poaceae), using flow cytometry and FISH

Abstract: Festuca subgen. Schedonorus is a group of broad-leaved fescues, which can be divided into two clades: European and Maghrebian. We employed fluorescent in situ hybridization —FISH— with probes specific for 5S and 35S ribosomal DNA and genome size estimation using flow cytometry to shed light on the determination of possible parental genomes of polyploid species of the Maghrebian clade. Our results indicate that octoploid F. arundinacea subsp. atlantigena probably originated from crossing of the tetraploids F. a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 69 publications
2
6
0
Order By: Relevance
“…This decrease in the monoploid genome size (i.e., in the DNA content divided by the ploidy level) observed at the highest ploidy levels would appear to be a general trend in angiosperms. Genome downsizing with polyploidy has been reported in Festuca and other Poaceae genera [12,27,51,52] and could result from genomic changes focused on reducing the negative effect of increased DNA content [53].…”
Section: Cytogenetic Variationmentioning
confidence: 99%
“…This decrease in the monoploid genome size (i.e., in the DNA content divided by the ploidy level) observed at the highest ploidy levels would appear to be a general trend in angiosperms. Genome downsizing with polyploidy has been reported in Festuca and other Poaceae genera [12,27,51,52] and could result from genomic changes focused on reducing the negative effect of increased DNA content [53].…”
Section: Cytogenetic Variationmentioning
confidence: 99%
“…Agriculturally most important are those species from the subgenus Schedonorus comprising broad-leaved fescues, the majority of which are polyploids, from tetraploids to decaploids ( Kopecký et al., 2008b ). Molecular and cytogenetic analyses have revealed that all these studied polyploid species arose from interspecific hybridization ( Humphreys et al., 1995 ; Catalán and Olmstead, 2000 ; Hand et al., 2010 ; Ezquerro-López et al., 2017 ); hence, they are of allopolyploid origin. All these allopolyploid species—including the tetraploids F. mairei , F. apennina , and F. glaucescens , hexaploid F. arundinacea , and octoploids F. arundinacea subsp.…”
Section: Control Of Chromosome Pairing In Polyploid Grassesmentioning
confidence: 99%
“…In plants, the monoploid genome size of polyploids is usually lower than that of their diploid or lower polyploid relatives due to a selective force or endogenous mechanisms favouring DNA loss after polyploidization (Leitch & Bennett, 2004;De Smet et al, 2013). The prevalent trend towards genome downsizing correlated with increasing ploidy level in polyploid series of closely related species (or within species) has been repeatedly confirmed in many plant genera, most recently, for example, in Aloe L. (Rao et al, 2015), Avena L. (Yan et al, 2016), Calligonum L. (Gouja et al, 2015), Chrysanthemum L. (Luo et al, 2017), Festuca L. (Ezquerro-L opez et al, 2017), Fragaria L. (Nosrati, 2015), Knautia L. , (Meudt et al, 2015). Considering this general trend, the opposite patterns observed in the Alyssum species under study could be attributed to the fact that they are not each others' closest relatives (Zozomov a-Lihov a et al, 2014;Spaniel et al, 2017a); however, there are also other possible explanations.…”
Section: Ploidy Levels and Genome Size Variationmentioning
confidence: 93%